Modelagem de circuitos fracamente n?o-lineares utilizando S?ries de Volterra - Carneiro, Tiago de Almeida (2005)
Abstract: The effects of non-linear distortions in weakly nonlinear systems were evaluated using the classical method of approach in power series. In recent years, the nonlinearities inherent in electronic devices have been characterized successfully using the Volterra method. The aim of the study was an exploratory study of this technique and apply it in the analysis of the effects typical non-linear in power amplifiers and verify its validity based on experimental data, previously known and using numerical simulations. is employing the Volterra method to perform mathematical modeling of power amplifiers, it managed to determine the power of the intermodulation products dissipated in the circuit output. With the help of this technique, one can also evaluate the compression characteristics in the system gain, as well as its frequency response and point of third order intercept.